Acid test : LSD, Ecstasy, and the power to heal - Shroder, Tom (Blue Rider Press, a member of Penguin Group (USA), 2014)
"A fascinating, transformative look at the therapeutic powers of psychedelic drugs, particularly in the treatment of PTSD, and the past fifty years of scientific, political, and legal controversy they have ignited, by award-winning journalist Tom Shroder"--